(untitled) - Graham, Douglas (Hoboken, N.J., 2004)
Have you ever had a great idea? Did you do anything with it? Don't worry-you are not alone. Most of us have had great ideas but few of us ever do anything about them. Ideation will tell you what to do, how to find out if anyone has thought of it before, how to protect, develop, fund, and market it-regardless of whether it's business, creative, or scientific in nature, and regardless of whether you are working in a large corporation or at home.
Keywords: Creative ability,Creative ability in business,Intellectual property